Synthesis, Characterization, Solution, Thermal and Dielectric Properties of 1,1´-Azobis(cyclohexanecarbonitrile) Initiated Copolymers of Methacrylonitrile and Vinyl Butyrate - RAJANI KUMAR, K.; FEROZ, S.K.; RAGHUNATH RAO*, P. (Asian Journal of Chemistry, 2024)
Copolymer of methacrylonitrile (MAN) with vinyl butyrate (VB) was synthesized by free radical polymerization using 1,1'-azo bis(cyclo-hexanecarbonitrile) (VAZO) as initiator in dimethyl formamide (DMF) at 60 ± 1 ºC. The monomer reactivity ratio was computed by both Fineman- Ross (F-R) and Kelen-Tudos (K-T) methods. The reactivity ratio values suggest the formation of random copolymers which has been supported by the azeotropic composition evaluation. The mean sequence length (n1 ) and probabilities (p) in the formation of various structural units were evaluated. The molecular weights of the polymers were determined by gel permeation chromatography, which increase with the increase of the copolymer of methacrylonitrile content. The solubility parameters were determined with the viscometric method. The glass transition tempe-rature (Tg) of the copolymers were determined by differential scanning calorimetry (DSC). Thermogravimetric analysis (TGA) of the copolymer was also studied. The dielectrical property of the copolymer is also studied.